THE ROLE OF FELDA IN SELF-ESTEEM AND SOCIAL NEEDS B40 MUSLIMS IN FELDA SABAH - Dicky Wiwittan Toto Ngadiman; Salmy Edawaty Yacoob; Hairunnizam Wahid (Journal of Islamic, Social, Economics and Development, 2018)
Employers have an important role in the effort to develop their self-esteem and social relationships. Self-esteem and social relationships are important needs as described by Maslow (1954). Therefore, the purpose of this study is to evaluate the perception of the employer's support and the level of involvement of Felda Group B40 in spiritual and social activities that can help to improve self-esteem and social relationships. This study involved 378 low-income people (B40) in Lahad Datu, Sabah. We used questionnaire in collecting the data and were analyzed using descriptive and scores mean values. The findings show that the level of perception of Felda B40 respondents who are indebted to the employer's support are moderate. Similarly, the level involvement of spiritual and social activities is moderate. As a result, this study can help employers in Malaysia and other parties to devise human resource development plans to improve their self-esteem and social relationships for them. We also discuss some implications and suggestions in this study